2019
DOI: 10.1371/journal.pone.0218436
|View full text |Cite
|
Sign up to set email alerts
|

The long term microbiota and metabolic status in patients with colorectal cancer after curative colon surgery

Abstract: Whether there are subsequent changes of metabolic profiles and microbiota status after partial colectomy remains unknown. We evaluated and compared long-term effects of microbiota status and metabolic profiles in early colorectal cancer (CRC) patients after curative colectomy to the controls. In this cross-sectional study, we analyzed metabolic syndrome occurrence in 165 patients after curative partial colectomy with right hemicolectomy (RH) or low anterior resection (LAR) and 333 age-sex matched controls. Fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…Studies have reported that CRC associated dysbiosis did not induce significant changes in the diversity or abundance of microbial communities [17,29]. However, several studies have reported reduced diversity in postoperative patients [24,25,30]. It is known that the use of antibiotics dramatically reduces the diversity of gut microbiota [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that CRC associated dysbiosis did not induce significant changes in the diversity or abundance of microbial communities [17,29]. However, several studies have reported reduced diversity in postoperative patients [24,25,30]. It is known that the use of antibiotics dramatically reduces the diversity of gut microbiota [27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, Lin et al [ 155 ] were the first to evaluate the long-term metabolic alterations and microbial composition in CRC patients after curative surgery. Metabolic syndrome was more prevalent among CRC patients after right hemicolectomy (RH) but not after lower anterior resection (LAR) compared to controls over a follow-up period of 5 years.…”
Section: Intestinal Microbiota and Long-term Outcomes Following Crmentioning
confidence: 99%
“…Since colon is the main reservoir of gut microbiome, surgical removal of colon may affect gut microbiome [31]. Indeed, right hemicolectomy for colorectal cancer has been reported to be associated with a decrease in diversity and richness of gut microbiome.…”
Section: Surgerymentioning
confidence: 99%
“…This rich community of microorganisms has co-evolved in a symbiotic relationship with humans. Its diversity is influenced by several factors including host genetics, mode of birth, age, gender, pregnancy, BMI, diet, medications, and surgery [12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The understanding of the gut microbiome evolves at a rapid pace, but the practical application of this knowledge is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%